System aspect of the sociological approach to research of social changes of the family - A. I. P’Yanov (Вестник Северо-Кавказского федерального университета)
The article analyzes the systemic aspects of the sociological approach to studying social changes in family functioning. The authors develops an independent conceptual scheme based on the understanding of the family as an anthropo-sociocultural system, where social changes of the functioning should imply the institutional, group, and individual levels